PERBEDAAN KEPATUHAN MINUM OBAT ANTARA LAKI - LAKI DENGAN PEREMPUAN DAN HUBUNGANNYA DENGAN KEBERHASILAN TERAPI PADA PASIEN HIPERTENSI DI KLINIK PELITA BUNDA KECAMATAN LUBUK PAKAM - DINDA ETIKA SURY; AHMAD HANDAYANI (LP2MTBM MAKARIOZ, 2021)
Data from World Health Organization (WHO) 2015 showed that around 1,13 billion of people in the world are affected byhypertension, more than 1 from 4 men and 1 from 5 women in the world affected by hypertension. Adherence to medicaltreatment has a very important role towards a successful therapy. Gender is a factor that affects in the utilization of healthservices and adherence to medical treatment. This research aimed to determine the difference in adherence to medicaltreatment between man and woman and the relationship with the success of the therapy in hypertensive patiens at PelitaBunda Clinic, Lubuk Pakam. This research is a cross sectional study. The total sample for this research is 50 hypertensivepatiens at Pelita Bunda Clinic, Lubuk Pakam with a purposive sampling method. Data were analyzed with Chi-Square test.The analysis using Chi Square obtained p-value=0,382 that shows no difference in adherence to medical treatment betweenman and women and the p-value <0,05 shows that there is a significant relationship between the adherence to medicaltreatment towards blood pressure. There is no difference in adherence to medical treatment between man and women.There is a significant relationship between adherence to medical treatment towards a successful therapy.